2022
DOI: 10.1016/j.pediatrneurol.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between MRI Scoring Systems and Neurodevelopmental Outcome at Two Years in Infants With Neonatal Encephalopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Additional findings, including intraventricular and subdural hemorrhage, are also scored. A recent study comparing the Barkovich, NICHD and Weeke scoring systems in relation to the neurodevelopmental outcome at 2 years of age, demonstrated that each of these approaches had good predictive value for cognitive and motor outcome in infants with HIE, but only the Weeke score was associated with language scores at 2 years [87].…”
Section: Scoring Systemsmentioning
confidence: 99%
“…Additional findings, including intraventricular and subdural hemorrhage, are also scored. A recent study comparing the Barkovich, NICHD and Weeke scoring systems in relation to the neurodevelopmental outcome at 2 years of age, demonstrated that each of these approaches had good predictive value for cognitive and motor outcome in infants with HIE, but only the Weeke score was associated with language scores at 2 years [87].…”
Section: Scoring Systemsmentioning
confidence: 99%
“…The NICHD scoring system has been validated for use in multicenter studies, has excellent interrater reliability (and our radiology investigators had high agreement with their scoring), and has been related to school-age neurodevelopmental outcomes [32]. While other scoring systems have been described [50-52], a recent comparative study demonstrated that scores were highly correlated and predictive abilities for motor and cognitive outcomes were comparable across systems [53]. Thus, we do not feel that our results would differ based on the selection of MRI scoring system used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The Barkovich score was the first scale validated for the stratification of brain injury severity in relation to neuromotor outcome [ 4 ]. The Barkovich score was associated with cognitive and motor outcomes at 2 years but failed to detect language difficulties at 2 years and mild brain lesions in comparison with the more detailed Weeke score, which requires diffusion-weighted imaging and proton MRS [ 33 , 34 , 35 ]. Due to the lack of proton MRS data in our cohort, the Weeke score could not be applied for the MRI analysis.…”
Section: Discussionmentioning
confidence: 99%